THE IMPACT OF GREEN BUSINESS, PACKAGING QUALIITY AND PRICE ON CONSUMER PURCHASE INTEREST OF MIXUE MSMEs - Hasanudin Hasanudin; Syamsudin Baharsyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
The high level of competition among retail MSMEs in selling contemporary beverages necessitates innovation and creativity among business owners in developing their sales strategies. The purpose of this study was to determine the influence of green business practices, packaging quality, and price on consumer purchasing interest of Mixue MSMEs in Bogor Regency. This study used a quantitative method with an associative approach, a type of research that aims to explain systematically, factually, and precisely the facts and characteristics of a particular object or population. The sampling technique in this study was non-probability sampling with a purposive sampling technique, which is a sampling technique based on specific considerations. The participating respondents were 45 people with the criteria of having purchased Mixue products more than 4 times, being at least 17 years old, following the @mixueindonesia Instagram account, and residing in Bogor Regency. The test tools used included data quality testing, classical assumption testing, influence testing, and hypothesis testing using SPSS 26 software. The test results show that the green business and quality variables partially influence the purchasing interest of Mixue MSME consumers in Bogor Regency. However, there is no reason to state that the price variable influences the repurchase interest of Mixue MSME consumers. The results also show that the green business, packaging quality, and price variables simultaneously influence the purchasing interest of Mixue MSME consumers in Bogor Regency.